PENGEMBANGAN LAYANAN LIBRARY TOUR PERPUSTAKAAN UNIVERSITAS SEBELAS MARET - Bambang Hermanto (Central Library of Universitas Sebelas Maret, 2020)
Libraries can make new breakthroughs to provide knowledge, insight and understanding of libraries. One of the service developments at the Sebelas Maret University Library is a library tour service. The aim of this service is to introduce libraries to the younger generation from an early age. The proverb says do not know then do not love. The meaning of the proverb can be used as a library driver to improve itself in the context of introducing services, collections, infrastructure, types of services and sources of information to the wider community. The library tour service will become a magnet for the public to visit the library. Library tour participants are given insights and knowledge about the ins and outs of libraries, the history of the establishment of Sebelas Maret University at the UNS Museum, around the campus, Radya Pustaka Library, Press Monument Library, Laweyan Batik, Surakarta Palace and Sangiran Museum.